Characterizing the Current State of Training Courses Available to US Disaster Professionals. (December 2019) - Kirsch, Thomas; Keim, Mark; Strauss-Riggs, Kandra
ABSTRACT: Objective: The objective of this study is to characterize US-based disaster training courses available to disaster response and disaster health professionals. Its purpose is to better inform policies and decision-making regarding workforce and professional development to improve performance. Methods: Courses were identified from 4 inventories of courses: (1) National Library of Medicine Disaster Lit database; (2) TRAIN National Learning Network; (3) Federal Emergency Management Agency (FEMA) National Preparedness Course Catalog; and (4) Preparedness and Emergency Response Learning Centers. An online search used 30 disaster-related key words. Data included the course title, description, target audience, and delivery modality. Levels of learning, target capability, and function were categorized by 3 expert reviewers. Descriptive statistics were used. Results: There were 3662 trainings: 2380 (65%) for professionals (53% for public health); 83% of the courses were distance learning, with 16% via classroom. Half of all trainings focused on 3 of 37 disaster capabilities and 38% of them were related to chemical, biological, radiological, nuclear, and explosives (CBRNE). The educational approach was knowledge-based for all courses and 99.6% imparted only lower levels of learning. Conclusion: Despite thousands of courses available, there remain significant gaps in target audience, subject matter content, educational approaches, and delivery modalities, particularly for health and public health professionals.